PRINCIPAL APPROACHES TO DEVELOPING THE NATIONAL QUALIFICATIONS FRAMEWORK IN GERMANY IN THE CONTEXT OF LIFELONG LEARNING - Galina A. Morozova (Образование и наука)
The paper gives an overview of the education system in Germany and explores the structure of National Qualifications Framework, developed in compliance with the Recommendations of the European Parliament and Council, and reflecting the specificity of the four-level educational structure. The author regards it as an effective means for educational system modernization and interaction with the labor market. Additionally, the research demonstrates the mechanisms, put forward by the Association for Developing the German Qualifications Framework to guarantee the compatibility and comparability of German and European qualifications; it also denotes the eight levels of German National Qualifications Framework along with their descriptors.The author believes that German experience of classification and systematization of qualifications in question can be used by Russian specialists.